Students Reading Interest at the Elementary Education Level: the Implementation of the School Literacy Movement in Banda Aceh - Desy Alfiah Na'im; Ramli Ramli; Mohd. Harun (Education Achievement: Journal of Science and Research, 2024)
The objective of this study is to describe the reading interest of students at the elementary education level in the implementation of the School Literacy Movement in Banda Aceh. A quantitative approach with a descriptive type was utilized. The population of this study comprises all students from MTsS Ulumul Qur'an, SMP Islam Al-Azhar Cairo Banda Aceh, and MTsN Model Banda Aceh, with a sample of 30 students, 10 students from each school. Data analysis techniques involved the use of questionnaires and descriptive statistics. The results of this study indicate that the reading interest of students at the elementary education level in the implementation of the School Literacy Movement in Banda Aceh is very good, with average reading interest scores of 79.88 for MTsS Ulumul Qur'an, 78.75 for SMP Islam Al-Azhar Cairo Banda Aceh, and 77.25 for MTsN Model Banda Aceh, all of which fall into the very good category. This high level of reading interest is supported by various literacy programs, including a 15-minute reading program, classroom library programs, best literacy class programs, library visit programs, and literacy hunting programs.